ANALISA PENGARUH TINGKAT SUKU BUNGA, INFLASI, KURS, DAN JUMLAH UANG BEREDAR TERHADAP VOLUME PERDAGANGAN SAHAM PADA LQ-45 - Fera Yuliana; Errin Yani Wijaya; Haryetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The capital market is one of investment alternative that able to yield optimal advantage for investor. Each investor is requiring of relevant information with transaction development in stock. This is very important to be made in consideration in compiling strategy and decision making of investment in capital market. The objectives of this research to analyze the influence of interest rate, inflation, exchang rate, and money supply to volume of stock trading on LQ-45 that listed on BEI in 2009-2012 periods.This research using time series data from IDX Statistic ICMD (Indonesian Capital Market Directory) and Indonesian Bank monthly published on BEI in January 2009 until December 2012. Population in this research is all company which included on LQ-45 that is 45 companies and number of samples 16 companies by passing phase purposive sample. Analyze technique to use in this research is multiple linier regression to obtain describe which totally regarding relationship between one variable with other variable. And use aplication Statistical Package For Social Sciences (SPSS) Statistics 21 program. The result of this reseacrh shows that interest rate variable has a negative and not significant to volume of stock trading, while inflation variable has a positive and not significant to volume of stock trading intrading, exchang rate and money supply variable has a negative and significant to volume of stock trading on LQ-45.Result of Adjuts R SquareKeywords : Volume of Stock Trading, Interest Rate, Inflation, Exchange Rates, Broad Money